Kontribusi Guru Pendidikan Agama Kristen dalam Menanamkan Teladan Religius Kepada Siswa Kelas VIII di SMP Negeri 1 Pangaribuan - Rita Berliana Sihite (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
There is a decline in student morality and the intention of student independence in carrying out worship. Christian Religious Education (PAK) teachers are very important in directing moral understanding and producing independence in worship. This study explores PAK teachers’ roles in facing moral challenges in the digital era. With a qualitative paradigm and a literature review approach, this study describes the roles of PAK teachers in shaping morals and spirituality as a form of interactive and contextual learning. The study results show that PAK teachers’ role is significant in shaping moral awareness and independence of worship. The role of PAK teachers is key to building a generation with a solid moral foundation and can carry out worship according to Christian teachings.